Perancangan Rangka Sepeda Motor Listrik dengan Simulasi Pembebanan Statik Menggunakan CFD - Farid Nurfianto; Pancatatva Hesti Gunawan; Yos Nofendri (METALIK : Jurnal Manufaktur, Energi, Material Teknik, 2026)
The simulation results indicate that all three frame designs meet structural safety standards with a minimum safety factor above 2.5, as established in previous studies. In the first design (V1), the safety factor ranges from 3.484 to 2.809. The second design (V2) shows an improvement in safety factor, ranging from 4.714 to 3.328. Meanwhile, the third design (V3) demonstrates the best performance with the highest safety factor, ranging from 4.785 to 3.379. The analysis also reveals that the V3 design has a more uniform stress distribution and displacement that remains within a safe limit, not exceeding 3.4311 mm. Validation was conducted by comparing the simulation results with manual calculations, showing minimal differences, confirming the validity of the simulation results. Based on the analysis, the V3 design is recommended as the optimal configuration due to its higher safety margin and better stress distribution compared to the other designs